Test on Hysteretic Behaviour of Prestressed Composite Joints with Concrete-Encased CFST Columns - Kun Wang; Huihui Luo (Advances in Civil Engineering)
Four composite joint specimens consisted of concrete-encased steel beams and concrete-encased concrete-filled steel tube (CFST) columns were tested under lateral cyclic loading, in which three specimens were prestressed and the other was not. In the tests, crack distributions and failure modes of the joint specimens were acquired, and the energy dissipation, rigidity degeneration, ductility, and residential deformation were investigated. Meanwhile, the strain variation of longitudinal rebars and I-steel flanges at beam ends as well as steel tubes in panel zones were analysed. The experimental results showed that a type of mixed mode consisting of shear failure in the panel zone and flexural failure at beam ends was found for three prestressed joint specimens, whilst only flexural failure at beam ends was observed for the non-prestressed one, and all joint specimens showed good hysteretic behaviour. In addition, as can be seen from the skeleton curves, the lateral peak loads of prestressed joint specimens could be enhanced to some extent by increasing the prestressing level, and the axial compression ratio had little effect on lateral loads; meanwhile, the ductility and energy dissipation for prestressed joint specimens also could be reduced by increasing the prestressing level and axial compression ratio.